How Bacteria Impact Host Nervous System and Behaviors: Lessons from Flies and Worms. - Masuzzo, A.; Montanari, M.; Kurz, L.; Royet, J. (Trends in Neurosciences, 2020)
Behavior is the neuronally controlled, voluntary or involuntary response of an organism to its environment. An increasing body of evidence indicates that microbes, which live closely associated with animals or in their immediate surroundings, significantly influence animals' behavior. The extreme complexity of the nervous system of animals, combined with the extraordinary microbial diversity, are two major obstacles to understand, at the molecular level, how microbes modulate animal behavior. In this review, we discuss recent advances in dissecting the impact that bacteria have on the nervous system of two genetically tractable invertebrate models, Drosophila melanogaster and Caenorhabditis elegans.